Review Artikel: Studi Farmakovigilans terhadap Kejadian Advers Drug Reactions (ADRs) - Hana Fadhilah; Salman Salman; Indah Laily Hilmi (Journal of Pharmaceutical and Sciences, 2023)
Pharmacoepidemiology studies drug use and drug effects in a large population. Pharmacovigilance or pharmacotherapy belongs to the field of pharmacoepidemiology, which is the study of collecting, detecting, assessing, understanding, and preventing side effects or problems related to the drugs used. Adverse Drug Reactions (ADRs) are unwanted responses from a drug that occurs at therapeutic doses of disease. Pharmacovigilance studies are conducted to prevent and reduce the incidence of ADRs in the community. This review article aims to determine the importance of pharmacovigilance studies on the incidence of ADRs in the community by identifying the incidence of ADRs that have causality with the disease. The method used is to search for article review sources by searching research journals and scientific articles related to pharmacovigilance studies in pharmacoepidemiology. Data from ten research journals related to pharmacovigilance studies yielded different results for analyzing ADRs. Many found that drugs or other factors influence the incidence of ADRs. ADRs can occur due to the patient's therapy for the disease he is suffering from and produce different complaints or effects in each patient. The literature study that has been carried out has created data related to pharmacovigilance studies on the incidence of ADRs, such as the incidence factors and the methods used. The incidence of ADRs can be reduced by applying pharmacovigilance and paying attention to the factors that cause ADRs.